2009
DOI: 10.1007/s10551-009-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Use of Pirated Software: A Contingency Model Integrating Perceived Risk with the Theory of Planned Behavior

Abstract: perceived risk, software piracy, theory of planned behavior,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 44 publications
10
106
1
8
Order By: Relevance
“…Based on the results, we found that the current study confirms the previous studies (e.g. Hsu and Lin, 2008;Liao et al, 2010;Lin, 2007;Teh and Yong, 2011). The employees of the hotels in Ambon show their intention to share their knowledge with others within their organisation.…”
Section: Hypothesis 6: the Knowledge Sharing Attitude Positively Affesupporting
confidence: 92%
“…Based on the results, we found that the current study confirms the previous studies (e.g. Hsu and Lin, 2008;Liao et al, 2010;Lin, 2007;Teh and Yong, 2011). The employees of the hotels in Ambon show their intention to share their knowledge with others within their organisation.…”
Section: Hypothesis 6: the Knowledge Sharing Attitude Positively Affesupporting
confidence: 92%
“…The TRA and TPR have been used extensively in Business Ethics research to evaluate links between intention and behaviour (Hassan, et al, 2014). Chosen examples include the prediction of dishonest actions (Beck & Ajzen, 1991); reporting unethical behaviour (Gibson & Frakes, 1997); differences between belief and action (Weber & Gillespie, 1998); and more recently, the use of ethics codes (Stevens, et al, 2005); digital piracy (Liao, et al, 2010) and the purchase intentions of ethically-minded consumers (Carrington, et al, 2010). According to TRA, belief (an individual's subjective probability of the consequence of a particular behaviour) affects attitude (a positive or negative feeling or disposition towards a particular behaviour), which in turn shapes an individual's behavioural intention (Ajzen, 1988;Ajzen, 1991Ajzen, , 2002Fishbein & Ajzen, 1975).…”
Section: The Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…All of the measurements use the newest questionnaires adapted from Vida et al (2012), Yoon (2011), Thurau, Henning, andSattler (2007), Liao, Lin, andLiu (2009), Panasand Ninni (2011), and finally from Garbharranand Thatcher (2009). The questions used are first translated into Indonesian language and then examined by conducting a pretest before being used as a research survey.…”
Section: Methodsmentioning
confidence: 99%
“…Perceived risk is an understanding about risks that can surface from a downloading activity or using illegal digital products like virus attacks, hacking, among others (Vida et al, 2012). In general, perceived risks can also be thought to be a way of thinking that arises from an uncertain feeling about the negative consequences that may occur (Liao, Lin, and Liu, 2010). This understanding about risk will increase in line with the level of uncertainty towards the negative consequences that may occur.…”
Section: Introductionmentioning
confidence: 99%